2020
DOI: 10.1029/2019pa003820
|View full text |Cite
|
Sign up to set email alerts
|

230Th Normalization: New Insights on an Essential Tool for Quantifying Sedimentary Fluxes in the Modern and Quaternary Ocean

Abstract: 230Th normalization is a valuable paleoceanographic tool for reconstructing high‐resolution sediment fluxes during the late Pleistocene (last ~500,000 years). As its application has expanded to ever more diverse marine environments, the nuances of 230Th systematics, with regard to particle type, particle size, lateral advective/diffusive redistribution, and other processes, have emerged. We synthesized over 1000 sedimentary records of 230Th from across the global ocean at two time slices, the late Holocene (0–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

8
2

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 268 publications
(438 reference statements)
1
71
0
1
Order By: Relevance
“…where 0.2429 and 1.3297 are constants to convert 232 Th from concentration in μg/g to activity in dpm/g and U from activity in dpm/g to concentration in μg/g, respectively, and (U/Th) AR is an estimation of the U/Th activity ratio of detrital material. A range of estimations is available for (U/Th) AR between 0.4 and 0.8; a value of 0.5 was used here, which is consistent with most other prior U/Th studies in the Atlantic sector of the Southern Ocean (Costa et al, 2020). The mean ± standard deviation of all detrital uranium corrections for the whole core was 9.5 ± 8.3% of the measured uranium.…”
Section: Methodssupporting
confidence: 76%
“…where 0.2429 and 1.3297 are constants to convert 232 Th from concentration in μg/g to activity in dpm/g and U from activity in dpm/g to concentration in μg/g, respectively, and (U/Th) AR is an estimation of the U/Th activity ratio of detrital material. A range of estimations is available for (U/Th) AR between 0.4 and 0.8; a value of 0.5 was used here, which is consistent with most other prior U/Th studies in the Atlantic sector of the Southern Ocean (Costa et al, 2020). The mean ± standard deviation of all detrital uranium corrections for the whole core was 9.5 ± 8.3% of the measured uranium.…”
Section: Methodssupporting
confidence: 76%
“…Modeling 230 Th in the ocean began with 1-D analytical models (Bacon & Anderson, 1982;Clegg et al, 1991;Nozaki et al, 1981;Nozaki & Horibe, 1983;Roy-Barman et al, 1996), which demonstrated that only reversible scavenging was able to reproduce the observations of both the dissolved and particulate vertical profiles. To explain complex (nonlinear) 230 Th profiles, more elaborate box models were developed that could account for different transport conditions and particle regimes under different ocean conditions, such as upwelling of deep water masses in the Southern Ocean (Chase et al, 2003;Roy-Barman et al, 2019;Rutgers van der Loeff et al, 2016;Rutgers van der Loeff & Berger, 1993;Venchiarutti et al, 2011), convection of deep water masses in the North Atlantic (Moran et al, 1995(Moran et al, , 1997Vogler et al, 1998), and lateral exchange between open ocean and ocean margin regimes (Anderson et al, 1983;Roy-Barman et al, 2009). More recently, 230 Th has also been integrated into complex geographic schemes in 2-D models (Luo et al, 2010;Marchal et al, 2000), in 3-D models of intermediate complexity (Henderson et al, 1999;Missiaen et al, 2019;Rempfer et al, 2017;Siddall et al, 2007Siddall et al, , 2005, and in global climate models (GCMs) (Dutay et al, 2009;Gu & Liu, 2017;Rogan et al, 2016;Van Hulten et al, 2018).…”
Section: Sediment Fluxes Under Lgm Climate Conditionsmentioning
confidence: 99%
“…This is in part because global models of dust input and iron dynamics still have significant uncertainties. Dust deposition models have few observational constraints over the open ocean, particularly in the South Pacific, given its remoteness from the continents and lack of well‐dated surface sediments (Albani et al, 2014; Costa et al, 2020; Kienast et al, 2016). Different global iron models vary over orders of magnitude in their simulated deposition rates from dust and in their average water column residence times of dissolved iron (Tagliabue et al, 2016).…”
Section: Introductionmentioning
confidence: 99%